Real time scheduling in distributed video servers - Mohamed Ghazzali. (2008)
This dissertation addresses the scheduling problem of video requests in a distributed video file server system. The objective of our scheduling technique is to increase the load balancing performance among the distributed video file servers and eventually, to minimize the delay for the video request objects to be serviced. In order to achieve this objective, we propose a load balancing algorithm called "NOVA " to perform dynamic scheduling of the video requests and to balance the load among the distributed video file servers so as to achieve an near optimal solution. We provide an experimental study in which our algorithm, compared to landmark algorithms, show improved performance in terms of load balancing, scalability and less delay for the video requests to be serviced.